Characterization of a Mycobacterium smegmatis Mutant Lacking Penicillin Binding Protein 1 - Billman-Jacobe, Helen (American Society for Microbiology, 1999)
The ponA gene of Mycobacterium smegmatis encodes a 95-kDa penicillin binding protein, PBP1, that is similar to PBP1s of Mycobacterium tuberculosis and Mycobacterium leprae. Transposon disruption of ponA in M. smegmatis resulted in a PBP1-deficient mutant that was sensitive to β-lactam antibiotics, was more permeable to glycine, and grew slowly in liquid culture.